Rise of the Central Bank Digital Currencies: Drivers, Approaches and Technologies - Raphael A. Auer; Giulio Cornelli; Jon Frost (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Central bank digital currencies (CBDCs) are receiving more attention than ever before. Yet the motivations for issuance vary across countries, as do the policy approaches and technical designs. We investigate the economic and institutional drivers of CBDC development and take stock of design efforts. We set out a comprehensive database of technical approaches and policy stances on issuance, relying on central bank speeches and technical reports. Most projects are found in digitised economies with a high capacity for innovation. Work on retail CBDCs is more advanced where the informal economy is larger. We next take stock of the technical design options. More and more central banks are considering retail CBDC architectures in which the CBDC is a direct cash-like claim on the central bank, but where the private sector handles all customer-facing activity. We conclude with an in-depth description of three distinct CBDC approaches by the central banks of China, Sweden and Canada.
Keywords: E42; E44; E51; E58; G21; G28; F31; 330; central bank digital currency; CBDC; payments; central banking; digital currency; digital money; distributed ledger technology; blockchain